Ich kann nicht anders: Social Heroism as Nonselfsacrificial Practical Necessity - Smyth, Bryan (Frontiers in Psychology, 2018)
Most self-reports of heroic action in both reactive and social (proactive) cases describe the experience as involving a kind of necessity. This seems intuitively sound, but it makes it unclear why heroism is accorded strong approbation. To resolve this, I show that the necessity involved in heroism is a nonselfsacrificial practical necessity. (1) Approaching the intentional structure of human action from the perspective of embodiment, focusing especially on the predispositionality of pre-reflective skill, I develop a phenomenological interpretation of Bernard Williams’ notion of “practical necessity” as an endogenous existential necessity. (2) I then offer a view of reactive heroism as instantiating this kind of necessity by literally embodying certain socially affirmed values in a way that is not self-sacrificial. This evinces a deep social bond, and it is this bond, rather than the action itself, is the ground of approbation. (3) I then discuss how this construal of reactive heroism can be extended to cases of social heroism by way of a necessity that is internal to the agent’s individual character. Similarly to reactive cases, a social hero literally embodies a certain ethical commitment such that her actions are likewise instances of nonselfsacrificial practical necessity. (4) I then discuss how the commitment perceived in cases of social heroism pertains to the actualization of “surplus validity,” such that whereas the reactive hero is praised for embodying shared value, the social hero is praised for embodying a commitment to actualizing the concrete potential of such value more fully The approbation accorded to social heroism is therefore tied inextricably to a normative judgment concerning such immanent progressive transformation.